INTEGRATION CONSTRUCTION OF MARINE UTILIZATION ELEMENTS TOWARDS INDONESIA GOOD OCEAN GOVERNANCE IN MARINE CADASTRE PERSPECTIVE - Yackob Astor; Widyo Nugroho SULASDI; Dwi Wisayantono; S. Hendriatiningsih (Indonesian Journal of Geospatial, 2015)
Abstract. Indonesia as an archipelagic country has marine larger area than land. With approximately consist of more than 13.466 islands (Geospatial Information Agency, 2013) and 99.093km coastline (Geospatial Information Agency, 2013), making Indonesia has more abundant natural resources of the sea than in land. This potential condition of marine resources is seen as an opportunity for Indonesia as a developing country to build excellence in coastal and marine field. However, after 70 years of its independence, maritime sector has not proved as a sector that can be seeded by the nation and relied by Indonesian people. Based on the literature, one of the main problems in Indonesian ocean is the unintegrated nature of utilization activities between institutional (sector), local government (provincial and city/county) and customary that caused overlapping claims marine areas that may result in marine boundaries conflicts.This paper discusses aboutintegration constructionconcept of marine utilization elements in Indonesia. Integration concept can be constructed by marine cadastre elements (right, restriction, and responsibility), integration principle and legal certainty principle in Law No. 4/2011 about Geospatial Information, Law 1/2014 about Coastal Management Areas and Small Islands, Law 23/2014 about Regional Autonomy, and Law 32/2014 about Marine.Keywords: right, restriction, responsibility, integration principle